Successful Rehabilitation of a 22-Year-Old Outpatient after Heart Transplantation with Severe Complications - Kandel, Michel (physioscience, 2018)
Background There is a consensus that exercise therapy is an important component in patient rehabilitation after heart transplantation (HTX). Recent studies showed that intensive interval training is more effective than low to moderate intensity training. Several studies described reinnervation of both the para- and sympathetic nervous system. The consequences of these findings have, however, not been implemented and up-to-date guidelines on exercise prescription in HTX do not exist. Furthermore, in clinical practice comorbidity and negative side-effects can aggravate the rehabilitation process after HTX.Objective This case report describes a successful individual rehabilitation programme.Method After an orthotope HTX A 22-year-old male patient suffered from severe complications with a cerebrovascular accident causing a hemiplegia and an acute both-sided renal failure. Massive restrictions in daily activities due to physical, social and psychological factors became apparent. Although these factors affected the rehabilitation process, they did not inhibit the successful application of an intensive interval exercise programme.Results/Conclusions Despite massive initial restrictions the patient well tolerated a consequent exercise therapy programme consisting of high intensity training and attained independency and a better quality of life level.
Keywords: heart transplantation; physiotherapy; rehabilitation; exercise